Diabetic Nephropathy in Children with Type 1 Diabetes: Clinical and Molecular Triggers of Development - Kovalchuk, Ihor; Burlaka, Ievgeniia (The Ukrainian Scientific Medical Youth Journal, 2025)
diabetic nephropathy is one of the severe microvascular complications of Diabetes Mellitus, Type 1, which can begin in childhood and significantly affect the further prognosis of patients. Despite significant progress in diagnosis and treatment, the incidence of this complication remains high, which necessitates the early detection and control of risk factors. The presented review analyzes studies that used both pediatric and adult registries to assess the impact of various risk factors on the development of Diabetic Nephropathy. Among the established risk factors, the most significant is the duration of diabetes. Family history of Type 1 and Type 2 diabetes and Diabetic Nephropathy significantly increases the risk of its development: in brothers and sisters of such patients, it is three times higher than in relatives of diabetic patients without nephropathy. Diabetic nephropathy is more prevalent among African American, Asian, and Native American populations compared to individuals of European descent. Genetic predisposition, sex, and puberty determine individual vulnerability to renal complications and can affect the rate of their progression. Among the modifiable prognostic factors, it is important to list Hypertension, Increased Body Mass Index, Dyslipidemia, and Microalbuminuria. In the ranking of risk factors, Hyperglycemia is considered the strongest factor. The presence of a pre-existing microvascular complication may contribute to the development of another complication in patients with Type 1 Diabetes.